Supporting Optimal Infant, Young Child and Maternal Nutrition and Health in Jordan: FY2023 1st Quarter Report October 1 - December 31, 2022. - Jordan Nutrition Innovation Lab. (Tufts University. Tisch Library., 2023)
The following is the first quarterly report of the Feed the Future Jordan Nutrition Innovation Lab for the fiscal year 2023 starting from October 1, 2022 until December 31, 2022.; Keywords: nutrition, research for development, capacity building, infant and child feeding practices, maternal nutrition.; Tufts University Friedman School of Nutrition Science and Policy Cooperative Agreement Associate Award No.: 72027820LA00003.